Constitutionality of monitoring and evaluation of regional regulation drafts and regional regulations by Regional Representative Council - Wido Haruni, Catur (Legality : Jurnal Ilmiah Hukum, 2022)
This research examines the constitutionality and legal implications of the DPD's new powers and duties in monitoring and evaluating regional regulation drafts in terms of the function of the DPD. The research method uses a normative approach and qualitative descriptive analysis. The results of the research show that the addition of the authority and duties of the DPD to carry out monitoring and evaluation constitutionally has no legal basis so the arrangement can be deemed unconstitutional. On the other hand, if the new authority arrangement for the DPD is seen as not contrary to the Constitution, then this will set a precedent so that the addition of the authority of the Regional Representatives Council is not only within the purview of supervision but it can also be carried out within that of legislation, without making changes to the constitution and simply through the Law. In terms of the legal implications of the authority and a new task of DPD to set the scope of monitoring and evaluation, monitoring and evaluation models, and overlapping authorities to conduct monitoring and evaluation with those in the Central Government, DPD cannot give any follow-up to monitoring results. Thus, restructuring the tasks and authority of the DPD in the constitution and the statute is a must.